De Novo Fatty Acid Synthesis During Mycobacterial Infection Is a Prerequisite for the Function of Highly Proliferative T Cells, But Not for Dendritic Cells or Macrophages - Stüve, Philipp; Minarrieta, Lucía; Erdmann, Hanna; Arnold-Schrauf, Catharina; Swallow, Maxine; Guderian, Melanie; Krull, Freyja; Hölscher, Alexandra; Ghorbani, Peyman; Behrends, Jochen; Abraham, Wolf-Rainer; Hölscher, Christoph; et al. (Frontiers in Immunology, 2018)
Mycobacterium tuberculosis (Mtb), the causative agent of human tuberculosis, is able to efficiently manipulate the host immune system establishing chronic infection, yet the underlying mechanisms of immune evasion are not fully understood. Evidence suggests this pathogen interferes with host cell lipid metabolism to ensure its persistence. Fatty acid metabolism is regulated by acetyl-CoA carboxylase (ACC) 1 and 2; both isoforms catalyze the conversion of acetyl-CoA into malonyl-CoA but have distinct roles. ACC1 is located in the cytosol, where it regulates de novo fatty acid synthesis (FAS), while ACC2 is associated to the outer mitochondrial membrane, regulating fatty acid oxidation (FAO). In macrophages, mycobacteria induce metabolic changes that lead to cytosolic accumulation of lipids. This reprogramming impairs macrophage activation, contributing to chronic infection. In dendritic cells (DCs), FAS has been suggested to underlie optimal cytokine production and antigen presentation, but little is known about the metabolic changes occurring in DCs upon mycobacterial infection and how they affect the outcome of the immune response. We therefore determined the role of fatty acid metabolism in myeloid cells and T cells during M. bovis BCG or Mtb infection, using novel genetic mouse models that allow cell-specific deletion of ACC1 and ACC2 in DCs, macrophages or T cells. Our results demonstrate that de novo FAS is induced in DCs and macrophages upon M. bovis BCG infection. However, ACC1 expression in DCs and macrophages is not required to control mycobacteria. Similarly, absence of ACC2 did not influence the ability of DCs and macrophages to cope with infection. Furthermore, deletion of ACC1 in DCs or macrophages had no effect on systemic pro-inflammatory cytokine production or T cell priming, suggesting that FAS is dispensable for an intact innate response against mycobacteria. In contrast, mice with a deletion of ACC1 specifically in T cells fail to generate efficient Th1 responses and succumb early to Mtb infection. In summary, our results reveal ACC1-dependent FAS as a crucial mechanism in T cells, but not DCs or macrophages, to fight mycobacterial infection.